A Puccinia striiformis f. sp. tritici Effector with DPBB Domain Suppresses Wheat Defense - Raheel Asghar; Yu Cheng; Nan Wu; Mahinur S. Akkaya (Plants)
Wheat (Triticum aestivum L.) is a primary crop globally. Among the numerous pathogens affecting wheat production, Puccinia striiformis f. sp. tritici (Pst) is a significant biotic stress agent and poses a major threat to world food security by causing stripe rust or yellow rust disease. Understanding the molecular basis of plant–pathogen interactions is crucial for developing new means of disease management. It is well established that the effector proteins play a pivotal role in pathogenesis. Therefore, studying effector proteins has become an important area of research in plant biology. Our previous work identified differentially expressed candidate secretory effector proteins of stripe rust based on transcriptome sequencing data from susceptible wheat (Avocet S) and resistant wheat (Avocet YR10) infected with Pst. Among the secreted effector proteins, PSTG_14090 contained an ancient double-psi beta-barrel (DPBB) fold, which is conserved in the rare lipoprotein A (RlpA) superfamily. This study investigated the role of PSTG_14090 in plant immune responses, which encodes a protein, here referred to as Pst-DPBB, having 131 amino acids with a predicted signal peptide (SP) of 19 amino acids at the N-terminal end, and the DNA sequence of this effector is highly conserved among different stripe rust races. qRT-PCR analysis indicated that expression levels are upregulated during the early stages of infection. Subcellular localization studies in Nicotiana benthamiana leaves and wheat protoplasts revealed that it is distributed in the cytoplasm, nucleus, and apoplast. We demonstrated that Pst-DPBB negatively regulates the immune response by functioning in various compartments of the plant cells. Based on Co-IP and structural predictions and putative interaction analyses by AlphaFold 3, we propose the probable biological function(s). Pst-DPBB behaves as a papain inhibitor of wheat cysteine protease; Pst-DPBB has high structural homology to kiwellin, which is known to interact with chorismate mutase, suggesting that Pst-DPBB inhibits the native function of the host chorismate mutase involved in salicylic acid synthesis. The DPBB fold is also known to interact with DNA and RNA, which may suggest its possible role in regulating the host gene expression.